Use of Social Networking Sites among Undergrade-level Women and its Effect on their Plans to Start a Business - Hossain, Tanjela; Iqbal, Md Mahbub; Shirazi, Hasan; Noor, Md. Asad (South Asian Journal of Social Sciences and Humanities, 2022)
This study looks at how Facebook, Twitter, and Instagram have impacted the business interests  of Bangladeshi college-aged women. The research methodology incorporates the technology  acceptance paradigm and a model of technology adoption and usage. The survey was developed,  checked for accuracy, and released to the public. According to the results, students' usage of  social networking sites affects their confidence in their capacity to succeed and their desire to do  so. These results have real-world and theoretical ramifications for policymakers and  entrepreneurial education, such as using widely used yet cutting-edge communication and  Internet tools to inspire young people to start their own businesses. In this analysis, we test the  hypothesis that there is a connection between the time spent on social networking sites (SNS)  and measures of confidence in, and desire for, starting one's own business. Over two hundred  and fifty female students from Private Universities in Bangladesh participated in online  questionnaires and correlation tests. More time spent on social networking sites is correlated with  more serious business thinking and behavior. Students of all sexes and all ages use Facebook, but  younger students and women in particular associate the platform with entrepreneurial aspirations  and attitudes more strongly than their male counterparts. There is a greater understanding of the relationship between social media presence and entrepreneurship factors because to this research.  The researchers sorted the interviewees' responses into four groups based on their findings: how  often they used SNS, how much they felt supported by SNS, how secure they felt in their  entrepreneurial conduct, and how ambitious they wanted to be as business owners’ Important  motifs were also determined for each class. Institutions of higher learning may and should use  social media to promote and educate aspiring business owners.
Keywords: Female Entrepreneurship; Social Media; Private University; Undergraduate and Women Empowerment